Obesity and Inflammation as Predictors of New-Onset Diabetes Mellitus after Kidney Transplantation - Karakan, Şebnem; Sezer, Siren; Acar, Özdemir; Nurhan, Fatma (Fırat University, 2013)
Objective: The clinical impact of new-onset diabetes mellitus (DM) after renal transplantation (RT) is frequently underestimated by clinicians. DM after transplantation is a leading risk factor for cardiovascular events. We aimed to identify post-RT risk factors for NODM. Materials and Methods: We retrospectively analyzed 236 non-diabetic patients (mean age 41±12 years; %75 male) between 1995 and 2008. We excluded those diagnosed as DM mellitus at RT time (n=23), greft loss during the two years (n =16), acute rejection, congestive heart failure, active infections (n =19), and those for whom data was not fully available (n=3). At 2 years of follow-up after RT, 34 (19.4%) patients developed DM (group 1). One hundred fourthy one non-diabetic patients were defined as group 2. We have recorded parameters at the time of DM diagnosis such as demographic features, medications, smoking history, blood pressure, daily proteinuria. Results: Age, body mass index, uric acid, sodium, LDL-cholesterol, CRP values were significantly higher in group 1. The percentage of weight gain (6.8%±5.2 vs. 5.2%±2.9, p=0.08) were similar in two groups. The prevalence of DM was similar between patients under CyA and TAC based immunosuppression. Conclusions: Baseline BMI, but not the weight gain at 2 years after RT, is an independent risk factor for DM. Importantly, overweight recipients within the high-risk group had raised inflammatory markers. Tailoring clinical strategies may minimize the impact of this complication.

Amaç: Organ naklinden sonra alıcıda yeni gelişen diabetes mellitus (DM) %50'e ulaşan oranda görülen metabolik bir komplikasyondur. Biz bu çalışmada kliniğimizde böbrek nakli sonrası yeni gelişen DM sıklığına katkısı olan faktörleri analiz edildi. Gereç ve Yöntem: Çalışmamızda 1995 ve 2008 yılları arasında böbrek nakli olan ve nakilden 2 yıl sonra greft fonksiyonu devam eden 236 (Ortalama yaş 41±12 yıl; %75 erkek) hastayı retrospektif olarak değerlendirdik. Böbrek nakli sırasında DM tanısı olanlar (n=23), nakil sonrası ilk 2 yıl içinde greft kaybı olanlar (n =16), akut rejeksiyon, konjestif kalp yetmezliği ve aktif enfeksiyonu olanlar (n = 19), ve bilgileri eksik olan hastalar (n=3) çalışma dışı bırakıldı. Böbrek naklinden 2 yıl sonraki takipte 34 hastada (%19.4) yeni gelişen DM tespit edildi (grup 1). DM tanısı almamış kalan 141 hastayı grup 2 olarak kabul ettik. Çalışmaya dahil edilen hastaların başlangıç ve DM tanısı aldığı zamana ait klinik, demografik özellikleri ve tüm laboratuvar özelliklerini kaydettik. Bulgular: Grup 1 hastaların yaş, Beden Kitle İndeksi (BKİ), ürik asit, LDL kolesterol, C-reaktif protein, değerleri istatiksel olarak grup 2 hastalarına göre yüksek bulundu. Her iki grupta 2 yılın sonunda kilo alım oranları eşit tespit edildi. (%6.8±5.2 ve %5.2±2.9, p=0.08). İmmunsupresif tedavilerine göre yapılan incelemede siklosporin ve takrolimus alan hastalarda yeni ortaya çıkan DM oranları eşit bulundu. Sonuç: Böbrek nakli olan hastalarda iki yılın sonunda kilo alım oranları etkili olmazken nakil esnasındaki BKİ oranları yeni ortaya çıkan DMi gelişiminde etkilidir. Risk faktörlerinin yakın takibi ve ortadan kaldırılması bu komplikasyonun görülme sıklığını azaltacaktır.
Böbrek Nakli Sonrası Yeni Diyabetes Mellitus Gelişmesine Etki Eden Faktörler; Obezite ve İnflamasyonun Rolü